1972
DOI: 10.1037/h0086728
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of psychotherapy for schizophrenic patients.

Abstract: Describes a study in which 2 forms of psychoanalytic psychotherapy, one not using medication and one using medication adjunctively, were contrasted with treatment by medication only. Ss were 36 16-49 yr. old schizophrenics who were randomly assigned to 3 treatment groups. Treatment was available to Ss for 20 mo. and an average of approximately 70 sessions. Ss were examined before treatment, and after 6, 12, and 20 mo. of treatment with the Rorschach, TAT, a clinical status interview, and a battery of intellect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

1974
1974
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…(The psychotherapeutic ward did not transfer any patients, but treated them all.) Empirical data to support the effectiveness of the specific psychoanalytic guiding conception presented above and employed in the case can be found in the Michigan State Psychotherapy Project (Karon & Vandenbos, 1972;. This project consisted of a randomized, controlled study of 36 schizophrenics, 16 to 49 years old, who were randomly assigned to three treatment groups: psychoanalytic therapy alone, psychoanalytic therapy with medication, and medication alone.…”
Section: Guiding Conception With Research and Clinical Experience Supmentioning
confidence: 99%
“…(The psychotherapeutic ward did not transfer any patients, but treated them all.) Empirical data to support the effectiveness of the specific psychoanalytic guiding conception presented above and employed in the case can be found in the Michigan State Psychotherapy Project (Karon & Vandenbos, 1972;. This project consisted of a randomized, controlled study of 36 schizophrenics, 16 to 49 years old, who were randomly assigned to three treatment groups: psychoanalytic therapy alone, psychoanalytic therapy with medication, and medication alone.…”
Section: Guiding Conception With Research and Clinical Experience Supmentioning
confidence: 99%
“…This study did not have any major methodological weaknesses from an experimental design perspective, but it has been criticized for its use of inexperienced psychotherapists (Karon & VandenBos, 1970;but cf. Tuma & May, 1974 Karon & VandenBos (1972 Yes 1 I Patients were randomly assigned to PD, PD-D, and D groups, but were not randomly assigned to experienced or inexperienced therapists. * Patients in the D group were those who elected to remain at the state hospital and were compared with the PD and PD-D groups, which were composed of those patients who consented to be transferred to a clinical research centre for treatment.…”
Section: Controlled Clinical Outcome Studiesmentioning
confidence: 99%
“…'s conclusion that the two treatments were essentially equivalent. Karon & VandenBos (1972 reported that psychodynamic treatment was superior to antipsychotic drug treatment. Serious methodological shortcomings limit generalizability from this study.…”
Section: Controlled Clinical Outcome Studiesmentioning
confidence: 99%
“…I think so. This response is ever made about the research findings from the Michigan State Psychotherapy with Schizophrenics Project (Karon & VandenBos, 1970, 1972, 1976, 1978, 1981. In this research project, an independent clinical assessment team conducted clinical interviews and psychological testing of potential patients for the research project.…”
Section: Grvandenbosmentioning
confidence: 99%